Physics of flow in porous media - Feder, Jens 1939-2019; Flekkøy, Eirik Grude 1963-; Hansen, Alex 1955- (Cambridge University Press, 2022)
An invaluable reference for graduate students and academic researchers, this book introduces the basic terminology, methods and theory of the physics of flow in porous media. Geometric concepts, such as percolation and fractals, are explained and simple simulations are created, providing readers with both the knowledge and the analytical tools to deal with real experiments. It covers the basic hydrodynamics of porous media and how complexity emerges from it, as well as establishing key connections between hydrodynamics and statistical physics. Covering current concepts and their uses, this book is of interest to applied physicists and computational/theoretical Earth scientists and engineers seeking a rigorous theoretical treatment of this topic. Physics of Flow in Porous Media fills a gap in the literature by providing a physics-based approach to a field that is mostly dominated by engineering approaches
Title from publisher's bibliographic system (viewed on 22 Sep 2022)
Keywords: Porous materials / Fluid dynamics; Hydrodynamik; Poröser Stoff; Strömung -- Mathematik